Vannamei shrimp cultivation technology as an innovation of coastal land use in Rugemuk village Pulau Labu sub-district Deli Serdang district in 2019 - Marsaulina, Irnawati; Marpaung, Harlem (Talenta Publisher, 2019)
This community service activity aims to increase the ability of fishermen and apply appropriate technology to cultivate Vannamei shrimp in a sustainable manner so that it will improve the welfare of fishermen's families. To achieve the objectives, several stages of activities are carried out, the first stage of the survey is to find out how the fish cultivator fishermen groups carry out their activities. The second stage is the socialization of activities that will be carried out to increase the ability to grow shrimp so that the results in a long time can increase the income (economy) of the fishermen. The third stage is to carry out coaching and counseling related to shrimp farming and can make decisions in the next economic field. This service program is carried out within 6 months. Program targets and outcomes (1). Increased knowledge and skills on appropriate technology in conducting Vannamei shrimp cultivation (2). Increased Vannamei shrimp yields by conducting shrimp culture training using tarpaulins. (3). In the long run, the results of aquaculture increase the economic welfare of the fishermen's family.